Determination of digestibility and digestible energy of kudzu (Pueraria phaseoloides) meal in the guinea pig (Cavia porcellus) - Cuibin, Ronald (2020)
The experiment was conducted to determine the digestibility coefficients and digestible energy of kudzu meal (Pueraria phaseoloides) in guinea pigs. Ten male guinea pigs of 12 weeks and 828 g of average weight were placed in metabolic cages. Five animals were fed the basal diet (wheat by-product) and the other five were fed with the experimental diet (60% wheat by-product and 40% kudzu meal). The indirect method was used for these determinations. The wheat by-product meal was used as a basal feed and its digestibility coefficient was determined by the direct method. There was a 14-day pre-experimental phase for the adaptation of the animals to the facilities and the new diet. The experimental phase was six days, in which the stool collection was performed. In both phases, feed consumption was measured daily. The apparent digestibility coefficients obtained were: 42.90% dry matter, 40.57% organic matter, 81.07% crude protein, 68.86% ethereal extract, 30.77% crude fibre, 30.55% nitrogen free extract and 74.18% ash. The digestible energy value determined by difference was 1.98 Mcal/kg of dry matter.